Analisis Tagmemik Bahasa Slang pada Komentar Akun Gosip TikTok - Sari, Desi Novita; Rustono, Rustono; Baehaqie, Imam (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2025)
The phenomenon of slang language is increasingly widespread on social media, particularly on the TikTok platform. One account that has attracted significant attention is Lambe Turah Official, which frequently presents gossip content and sparks numerous comments from netizens. The gossip account Lambe Turah Official has millions of followers and consistently produces viral content. The comment section of this account is filled with various forms of netizens’ expressions, often characterized by the use of distinctive slang. This study aims to analyze the syntactic structure of slang sentences found in the comments on this account. The data were obtained from screenshots of netizens’ comments on posts by Lambe Turah Official on TikTok. The analysis was carried out using a syntactic approach, focusing on the tagmemic syntactic structure and the socio-linguistic functions of slang in TikTok comments. The phenomenon of slang use in the Lambe Turah Official comment section not only represents a form of linguistic creativity but also emphasizes the social functions of language as a marker of group identity, a medium of solidarity, and a vehicle for criticism or satire expressed in a casual linguistic style. From a syntactic perspective, slang sentences show that even though they do not always conform to standard language rules, their structure remains comprehensible to the user community due to shared social context and understanding.